CONTINGENCY FACTORS AND MANAGEMENT ACCOUNTING PRACTICES OF LISTED MANUFACTURING FIRMS IN LAGOS STATE - Mustapha Abdulrasaq; Abdullahi Adio Babatunde; Isaac Biodun Ogunshola (Malete Journal of Accounting and Finance)
Given the critical roles of management accounting information in supporting managerial functions, its usage, to optimize organizations values, must be aligned with firm’s characteristics or contingencies. The extent to which firms’ contingency factors are being considered in the choice of management accounting practices is the focus of this study. Specifically, this research investigated the variation in management accounting practice as explained by Perceived Environmental Uncertainty (PEU), firms age, discipline of management. Cross-sectional research design was employed to collect surveyed data from randomly selected 327 senior management staff of manufacturing companies in Lagos. The obtained data through closed-ended questionnaire was analyzed using descriptive statistics (proportion and measure of central tendency) and inferential statistics (multiple regression analysis) to estimate predictors. The results revealed findings that PEU (β = 0.387 ˂ 0.05), discipline of management (β = 0.257 ˂ 0.05) and firms’ age (β = 0.431 ˂ 0.05) significantly influence the level of at which management accounting techniques are put to use in generation information to perform various functions. On the basis of reported findings, the conclusions were: firms that are perceiving high level of environmental uncertainty make use of management accounting technique more often as well firms that have spent longer years in the business. Similarly, top management that have qualifications in management-related courses extensively make use of management accounting techniques. Given this conclusion, the study recommends that as level of uncertainty in environment increase firms should generate more accounting information to monitor the environment. It is important for management that as firms are growing older, extensive use of management accounting should be encouraged to effectively manage complexity inherent in firm’s expansion and finally, management should try to acquired more managerial skills to improve the optimum use of management accounting techniques